Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Equity Pada Perusahaan Sektor Manufaktur Yang Terdaftar Di Bei Periode 2020-2024 - Muhammad istiqlaluddin Akbar; Mustain Saputra (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to examine the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Equity (ROE) in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research uses a quantitative approach with secondary data obtained from annual financial statements. The sampling technique employed purposive sampling, with a total of six companies selected based on specific criteria. Data analysis was conducted using multiple linear regression and classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroskedasticity tests. The results show that the Current Ratio has a significant effect on Return on Equity, while the Debt to Equity Ratio also affects ROE, although to a lesser extent. The regression model meets all classical assumption requirements, confirming the validity of the analysis. In conclusion, a company’s liquidity and capital structure play a crucial role in determining its profitability level, and should therefore be managed effectively to enhance financial performance and attract investors.